Ein tingas lydhøyre mann Arvid Torgeir Lie - ein tekstbiografi - Nordstoga, Sveinung (Spartacus Forlag AS / Scandinavian Academic Press, 2023)
Arvid Torgeir Lie (1938-2020) is among the leading Norwegian poets in the post-war period - original, innovative, surprising and highly valued by fellow writers.With a background in the mining community Åmdal's mine in Tokke municipality, he wrote poems inspired by the haiku tradition, labor poems, landscape poems and also more civilization-critical poems about media development. The lyrics reflect the environment he grew up in, with a strong sense of community, but he also engages in dialogue with tradition and seeks a genuinely informal, oral and disarming poetic expression. In this book, Sveinung Nordstoga draws several lines through his entire authorship, which in addition to eleven collections of poems also contains translations, a collection of short stories and an unpublished play.